(untitled) (Web of Teachers: Inderscience Research, 2024)
In this article, we have considered the current problems in the teaching of chemistry in Uzbekistan and offer innovative solutions to improve the educational experience. Analyzing the current educational system and the specific socio-cultural context, the article is about how to motivate students, improve lesson design and include laboratory experiments in the curriculum, use virtual laboratories, artificial intelligence, AR and VR technologies in the classroom. proposes strategic measures.